Alterations of T cell receptor Vβ repertoire of CD8 T lymphocytes in immune tolerance induction in two hemophilia A patients with inhibitors - Sakurai Yoshihiko; Matsutani Takaji; Yoshioka Takeshi; Takeda Tomohiro; Yoshioka Akira; Shima Midori (Vojnosanitetski Pregled)
Background/Aim. Hemophilia A patients with inhibitors are treated effectively with immune tolerance induction (ITI) therapy. Although anti-idiotypic antibodies may play a certain role in the underlying mechanism, the detailed mechanism by which ITI produces a curative effect remains unknown. The aim of this study was to clarify the immunological aspect of ITI. Methods. Longitudinal T-cell receptor (TCR) analysis was performed during ITI. TCR variable region α-chain and β-chain repertoires were serially analyzed for peripheral blood mononuclear cells (PBMCs), CD4 T cells, and CD8 T cells from 2 hemophilia inhibitor patients treated with ITI (Patients 1 and 2). Furthermore, to see whether skewing observed in TCR analysis resulted from clonality alterations, T-cell clonality was investigated using complementarity-determining region 3 (CDR3) size spectratyping. Results. In the patient 1, inhibitor titer remained to be 19.6 BU/mL for 596 days after ITI commencement, and ITI was unsuccessful. In the patient 2, inhibitor titer disappeared 434 days after ITI commencement, and ITI was successful. In both cases, skewing of TCR variable region α/β-chain repertoires was observed in CD8 T cell subset, whereas not in CD4 T cell subset. Conclusion. Alteration of TCR repertoires, especially TCR variable region β-chain repertoire of CD8 T cells, was distinct between successful and unsuccessful cases, suggesting that immunological response in the early phase affected the ITI outcomes.